Contrasting pattern of subtelomeric satellites in the Cannabaceae family - Horáková, Lucie; Bačovský, Václav; Čegan, Radim; Janoušek, Bohuslav; Patzak, Josef; Hobza, Roman (Frontiers in Plant Science, 2025)
IntroductionSatellite DNA (satDNA) is a rapidly evolving component of plant genomes, typically found in (peri)centromeric, (sub)telomeric, and other heterochromatic regions. Due to their variability and species- or population-specific distribution, satDNA serves as valuable cytogenetic markers for studying chromosomal rearrangements and karyotype evolution among closely related species. Previous studies have identified species-specific subtelomeric repeats CS-1 in Cannabis sativa, HSR1 in Humulus lupulus, and HJSR in Humulus japonicus. These satellites have been used to differentiate sex chromosomes from autosomes, however, their evolutionary origins, sequence variation and conservation pattern across related species remain largely unexplored.MethodsIn this study, we analyze sequence similarity among these satellites and assess their interspecific chromosomal localization using fluorescence in situ hybridization (FISH).ResultsOur results reveal that the HSR1 and HJSR satellites are shared across all studied species, suggesting their common origin from a shared pool of satDNA in their common ancestor. In contrast, the CS-1 satellite exhibits higher sequence divergence.DiscussionAlthough all three satellites are predominantly localized in subtelomeric regions, we identified species-specific exceptions. These findings provide new insight into the evolutionary dynamics of satDNA within the Cannabaceae family and offer further support for the divergence of Humulus species.